Signal transduction by leukocyte receptors - Dushek, Omer (Henry Stewart Talks, 2021)
An overview of signalling pathways, Signal transduction by T cell receptors, The role of co-signalling receptors, TCR activation, The role of ZAP-70, Mechanism of LFA-1 co-stimulation, Mechanism of CD28 co-stimulation, Mechanism of PD-1 and BTLA co-inhibition, Signal transduction by TNF-receptors